2018
DOI: 10.12691/jfnr-6-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Study on Sponge Cake Qualities Made from Hen, Duck and Ostrich Eggs

Abstract: This study compared hen, duck and ostrich eggs on the physicochemical characteristics of sponge cakes.Hen egg white exhibited a higher overrun and foam stability. The sponge cakes elaborated with hen eggs provided softer texture, higher volume and higher overall acceptability, despite duck egg white had higher foam stability than that of ostrich egg white, whereas duck egg gave harder cake texture than that of ostrich. Sponge cakes made from hen and ostrich eggs had higher L value, while cakes made from duck e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Nonetheless, yolk and albumen are both equally important in cake making. For instance, Hwang et al 1 showed that the uses of chicken, duck and ostrich eggs led to different foaming for sponge cakes. These eggs differ in egg weight, yolk colour and albumen quantities 6 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, yolk and albumen are both equally important in cake making. For instance, Hwang et al 1 showed that the uses of chicken, duck and ostrich eggs led to different foaming for sponge cakes. These eggs differ in egg weight, yolk colour and albumen quantities 6 .…”
Section: Resultsmentioning
confidence: 99%
“…The cake industry consumes a lot of eggs because the eggsʼ yolks' carotenoids influence the overall cake colour 1 . So, due to their important carotenoid content coupled with an important antioxidant property, many plant-coloured grains are added to poultry feed 2 .…”
Section: Introductionmentioning
confidence: 99%